Dimensions Of Consumer Protection In Criminal Law Perspective And Islamic Economic Law Perspective - Alviani Vinsensia Simarmata; Pujiyono Pujiyono (Jurnal Hukum Prasada, 2019)
Indonesia has a function as an organizer of public welfare, one of which is an effort to realize consumer protection.The purpose of this study is to determine consumer protection from the perspective of criminal law and the perspective of Islamic economic law This research uses a normative juridical method, to answer the main problem, namely how consumer protection in the KHUP perspective and Islamic economic law. This research found the definition of consumers regulated in the Law on consumer protection has a narrower meaning than the meaning of business actors (unbalanced). A balanced understanding of both will bring a positive influence on consumer coverage that must be protected as regulated in Islamic law. Islamic law and the Criminal Code both regulate the problem of consumer protection to create benefit, justice, balance, security and safety and guarantee legal certainty. The difference is that Islamic law reveals the values of religiosity by not putting aside social and humanitarian values (vertical and horizontal relations / habibum minallah wa hablum minannas), while the Criminal Code shows more social and humanitarian values (horizontal relations / hablum minannas) so that provide legal certainty.